2013
DOI: 10.1007/s00421-013-2675-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of neuromuscular fatigue on the electromechanical delay of the leg extensors and flexors in young and old men

Abstract: These findings showed differential fatigue-induced EMD recovery patterns between the leg extensors and flexors with the flexors being slower to recover and also that age-related increases of EMD are muscle group specific. The sustained increased EMD of the flexors during recovery may have important injury and performance implications in a variety of populations and settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 56 publications
3
62
2
2
Order By: Relevance
“…Differences in electromechanical delay across muscles is a more complicated issue (Corcos et al, 1992;Hug et al, 2011). While studies have shown that the delay may be muscle dependent (Conchola et al, 2013), we were able to achieve sufficiently accurate timing of joint moments and powers without such added complexity. Furthermore, previous studies have used a single electromechanical delay across muscles and subjects and obtained reasonable results (Lloyd and Besier, 2003;Arnold et al, 2013).…”
Section: Electromyography Parameter Optimizationmentioning
confidence: 85%
“…Differences in electromechanical delay across muscles is a more complicated issue (Corcos et al, 1992;Hug et al, 2011). While studies have shown that the delay may be muscle dependent (Conchola et al, 2013), we were able to achieve sufficiently accurate timing of joint moments and powers without such added complexity. Furthermore, previous studies have used a single electromechanical delay across muscles and subjects and obtained reasonable results (Lloyd and Besier, 2003;Arnold et al, 2013).…”
Section: Electromyography Parameter Optimizationmentioning
confidence: 85%
“…The process of muscle contraction involves an electromechanical delay (EMD), which is traditionally measured as the time lapse between the onsets of electrical activity and force production . Previous studies demonstrated that EMD is an effective and useful measure for assessing changes associated with muscle fatigue, muscle damage, musculotendinous stiffness, aging, and identification of gender‐related physiological and functional differences . EMD is thought to be influenced by several factors, including propagation of action potentials across the muscle membrane, excitation‐contraction coupling (EC‐C), and stretching of the series elastic component (SEC) .…”
mentioning
confidence: 99%
“…There are conflicting reports about the influence of fatiguing exercise on EMD. Some studies have indicated that fatigue imposed by isometric [17], eccentric and concentric isokinetic contractions [34] leads to strength loss, which augments the EMD. However, as demonstrated in ours and other studies [39] neither of the assessed muscles had their EMD compromised by downhill running.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Conchola et al [17] showed that fatigue induced by intermittent isometric contractions lengthened both the KF and KE EMD. However, this lengthening lasted longer for the KF than for the KE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation